'I want my sovereignty back!' A comparative analysis of the populist discourses of Podemos, the 5 Star Movement, the FN and UKIP during the economic and migration crises. Issue 7 (3rd October 2019) - Borriello, Arthur; Brack, Nathalie
ABSTRACT: The multiple crises that the EU has faced over the last decade have provided fertile ground for the emergence of new political movements, often labelled as 'anti-system', 'populist' and 'Eurosceptics'. One defining characteristic of these parties is their claim to represent 'the people' and their reliance on the idea of sovereignty. This article aims at examining how these populist parties have framed sovereignty in relation to the economic and migration crises. It argues that the binary opposition between EU integration and national sovereignty does not tell the whole story, and that the populist upsurge reflects instead competing versions of sovereignty at the national level. To test this hypothesis, we conduct a corpus-based analysis of the discourse of four leading populist parties between 2012 and 2017: the Front National, the UK Independence Party, the Movimento cinque Stelle and Podemos.